An Analytical Study Of The Impact Of The Tax Burden On The Standard Of Living Of The Family In Lattakia Governrate - يــمن منصور; محمد عنتر (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This research aims to provide solutions and suggestions that will help those concerned to make decisions that reduce the impact of this burden and contribute to improving the standard of living, also aimed to identify the reality of the tax system in Syria, and compare the specific tax burden in Syria with the tax burden determined according to international standards. The results showed a statistically significant effect the tax burden on the standard of living, and there is a statistically significant effect of the salary and wages tax on the standard of living if the family, there is a statistically significant effect of income tax on the standard of living of the family, there is a statistically significant effect of other tax(real estate tax, car tax) on the standard of living of the family, there are fundamental differences between the tax burden specific in Syria and the tax burden specific accordance with international standards.